PENGARUH WORKING CAPITAL TO TOTAL ASSETS, CURRENT LIABILITIES TO INVENTORIES, OPERATING INCOME TO TOTAL LIABILITIES, TOTAL ASSETS TURNOVER, NET PROFIT MARGIN & GROSS PROFIT MARGIN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MAKANAN & MINUMAN DI INDONESIA - Unimal, Iswadi (JURNAL KEBANGSAAN, 2015)
This research aims to provide the emprical evidence about the influence of Capital to Total Assets (WCTA), Current Liabilities to Inventories (CLI), Operating Income to Total Liabilities (OITL), Total Assets Turnover (TAT),Â  Net Profit Margin (NPM), Gross Profit Margin (GPM) toward earnings growth. The data used in this reseach is financial statements data of food and beverage companies in the priod of 2008-2012 in BEI. the data was collected from www.idx.co.id. The data analyzed by using multiple regression method in form of verificative research. The result of this research shows that WCTA, CLI, OITL and TAT have no sigificant influences on earnings growth, NPM positively significant influences on earnings growth and GNP negatively significant influences on earnings growth.Â Keywords : earnings growth, WCTA, CLI, OITL, TAT, NPM, GPM